Description And Composition Chemistry of Meat and Carapace (Thalasina Anomala) - Ghazali, Tengku Muhammad; Sitinjak, Fillia R.G; Simanullang, Wahdi (Jurnal Perikanan dan Kelautan, 2020)
Thalasina anomala is a type of shrimp that is generally found in the muddy areas of the mangrove area on the coast of the Selat Panjang. The purpose of this study was to obtain the chemical composition of meat and carapace and the rendemen of T. Anoma. Meat and carapace as raw material. This research method description and data analyzed statistically. In this study, there are two stages, namely preparation and rendement of body parts of rama shrimp and then proximate analysis of meat and carapace. Proximate test results from meat and carapace of successive shrimp are water content 76.58 %, 38.93 % gross weight (gw), protein content 81, 46 %, 10.12 % dry weight (dw) , fat content of 5.01% (dw), 2.36% (dw), ash content of 3.93% (bk), 73.96% (dw) and Carbohydrates 9.61% (dw), 14.62% (dw). This value shows that protein in meat is beneficial in food, while carapaces ash content shows the high mineral content